Procedures and Interventions for Drug Addict Rehabilitation in an Islamic Perspective: A Spiritual, Psychological, and Social Approach - Nurhillal Bestari; Hairunnas H (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Drug abuse is a multidimensional problem that affects the physical, psychological, social, and spiritual aspects of individuals, requiring a comprehensive and sustainable rehabilitation approach. This study aims to analyze the procedures and interventions of drug addict rehabilitation from an Islamic perspective through spiritual, psychological, and social approaches, as well as to identify their contributions to the recovery process of drug addicts. This research employed a library research method with a descriptive qualitative approach by collecting data from books, scientific journal articles, and various academic sources relevant to Islamic-based rehabilitation. The data were analyzed using content analysis techniques to identify concepts, patterns, and research findings related to rehabilitation procedures and intervention models. The findings indicate that Islamic-based rehabilitation is conducted through several stages, including detoxification, spiritual guidance, Islamic psychological therapy, social development, and community reintegration. Spiritual interventions such as dhikr, prayer, fasting, Sufi therapy, and moral development were found to enhance emotional stability, self-control, religious awareness, and reduce the risk of relapse among former drug addicts. In addition, family support and a positive social environment play important roles in the success of rehabilitation. This study concludes that Islamic-based rehabilitation provides both theoretical and practical contributions to the development of a more holistic, humane, and recovery-oriented rehabilitation model.